Anti-infective potential, chemical profile, and molecular docking investigation on antioxidant-rich fraction of Murraya koenigii against Gram-negative pathogenic bacteria - Haris, Zarrin; Ahmad, Iqbal; Munawar, Nayla; Adil, Mohd; Alandiyjany, Maher; Husain, Fohad Mabood (Frontiers in Microbiology, 2026)
PurposeTo assess the antioxidant-rich fraction of Murraya koenigii for its anti-infective properties against Gram-negative pathogenic bacteria by in vitro and in silico approaches.ResultsThe most antioxidant active fraction, i.e., M. koenigii chloroform fraction (MKCF), significantly reduced violacein production (70.73%) in Chromobacterium violaceum 12,472. Significant reduction in prodigiosin production, protease activity, and swarming motility of Serratia marcescens, and other tested virulence factors of Pseudomonas aeruginosa PAO1 was recorded. More than 60% reduction in biofilm formation was recorded against test pathogens, indicating broad-spectrum anti-infective activity. SEM and CLSM imaging revealed alterations in the structure of the biofilm. Major key compounds such as Gibberellic acid, methyl ester, 7,8-Epoxylanostan-11-ol, 3-acetoxy were detected by GC/MS, and numerous compounds in MKCF were identified using LC-qTOF/MS analysis. In silico analysis revealed morellin and murrayazolinol with good binding affinity with CviR and EsaI, with binding energies of −9.07 and −9.17 kcal mol−1, respectively.ConclusionThe most active antioxidant fraction, i.e., MKCF, could be exploited as an anti-infective agent against Gram-negative bacterial pathogens, attenuating virulence and pathogenicity. Further, in vivo efficacy of the active fraction/phytocompounds needs to be evaluated to explore the therapeutic potential of MKCF.